Management of grain smut (Macaipinomyces sharmae) in little millet - S.K. TRIPATHI, A.K. JAIN* and (Indian Phytopathology, 2007)
Grain smut caused by Macalpinomyces sharmae is a serious disease of little millet and inflict considerable reduction in grain yield. Average grain smut incidence ranging from 5.9 to 31.0% and 5.0 to 7.8% was recorded in fields at Rewa and Dindori centers of Madhya Pradesh during 1997 to 2005. Early maturing cultivars (up to 70 days) namely OlM 20, OlM 23, OlM 45, DlM 80, DlM 93, DlM 314, DlM 369, RlM 36 and JK 8 were found susceptible to grain smut. Cultivars having more than 100 days maturity period were found completely free. Reduction in grain yield plant was recorded 9.8 to 53.55 % in different cultivars, where as, reduction in plant height was 4.2 to 16.6% and in panicle length 6.4 to 38.9%. Seed treatment with carboxin @ 2 g kgÂ·1 seed + one foliar spray of carbendazim (0.05%) was found most effective followed by seed treatment + one foliar spray of carbendazim. (0.05%), but highest B:C ratio was recorded in seed treatment alone with carboxin or carbendazim @ 2 g kgÂ· 1seed.